Multimodal transport in Kosovo - Jashari, Nexhat (Array, 2018)
Development of the classic branches of transport until after the year 1999 was a characteristic of economic policies in Kosovo, which came as a result of improper functioning of the market economy and non-application of modern technologies.Despite the great importance that the multimodal transport has for Kosovo, till today initial steps have been taken with the approval of the sector strategy for the multimodal transport 2015-2025 by the Kosovo Government, respectively by the Ministry of Infrastructure. The aim of this strategy is to set priorities in terms of infrastructure, as well as in terms of legal regulation. This paper addresses this topic in Kosovo for the first time, among other things notes the newly established circumstances in Kosovo after the war in 1999, which led to the change of policy development in the field of transport in order to adapt to the newly created circumstances and approximate with EU integration processes.